Ina marri u qan ṭuppi : Par la bêche et le stylet! : cultures et sociétés syro-mésopotamiennes : mélanges offerts à Olivier Rouault - Abrahami, Philippe,; Battini, Laura,; Rouault, Olivier, (Archaeopress ancient Near Eastern archaeology ;, 2019)
25 papers written by colleagues, friends and former students pay tribute to the career of Professor Olivier Rouault who has conducted extensive research in the fields of both Assyriology and Ancient Near Eastern archaeology.